If a 1 , a 2 , ⋯ a 4 0 0 1 are in Arithmetic Progression
and a 1 a 2 1 + a 2 a 3 1 + ⋯ + a 4 0 0 0 a 4 0 0 1 1 = 1 0
and a 2 + a 4 0 0 0 = 5 0
Evaluate ∣ a 1 − a 4 0 0 1 ∣
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice Solution. Thanks
Log in to reply
What was your way?
This was a nice problem, but overrated in my opinion.
good problem and good solution(same as I did).
The answer is (+30) or (-30)
it must be positive
Every term a n a n + 1 1 can be written as r 1 ∗ ( a n 1 − a n + 1 1 ) , where r is the common difference of the progression. Thus, we can rewrite the sum as:
r 1 ∗ ( a 1 1 − a 2 1 + a 2 1 − a 3 1 + … + a 4 0 0 0 1 − a 4 0 0 1 1 ) = 1 0
It follows that: a 1 1 − a 4 0 0 1 1 = 1 0 r
a 1 ∗ a 4 0 0 1 4 0 0 0 r = 1 0 r
a 1 ∗ ( a 1 + 4 0 0 0 r ) = 4 0 0 (Equation I )
Now, from the condition a 2 + a 4 0 0 0 = 5 0 , we derive the following:
2 a 1 + 4 0 0 0 r = 5 0
4 0 0 0 r = 5 0 − 2 a 1 (Equation I I )
Plugging the result of I I back in I , we get:
a 1 ∗ ( 5 0 − a 1 ) = 4 0 0
a 1 2 − 5 0 a 1 + 4 0 0 = 0
Solving for a 1 yields: a 1 = 4 0 or a 1 = 1 0
If a 1 = 4 0 , then 4 0 0 0 r = − 3 0 and so a 4 0 0 1 = 1 0
If a 1 = 1 0 , then 4 0 0 0 r = 3 0 and so a 4 0 0 1 = 4 0
In either case, ∣ a 1 − a 4 0 0 1 ∣ = 3 0 .
Let N = 4 0 0 0 as a shorthand. We have an arithmetic progression a k = a 1 + ( k − 1 ) d and need to calculate ∣ x ∣ : = ∣ a 1 − a N + 1 ∣ = N ∣ d ∣ . The first equation yields a telescope sum:
1 0 ⇒ 1 0 N = k = 1 ∑ N a k a k + 1 1 = k = 1 ∑ N ( a 1 + ( k − 1 ) d ) ( a 1 + k d ) 1 part. frac. = k = 1 ∑ N a 1 + ( k − 1 ) d d 1 − a 1 + k d d 1 = d 1 k = 1 ∑ N a k 1 − d 1 k = 2 ∑ N + 1 a k 1 = d a 1 1 − d a N + 1 1 = d a 1 1 − a 1 + N d 1 = a 1 ( a 1 + N d ) N = a 1 ( a 1 + N d )
The second equation yields
5 0 = a 2 + a N = 2 a 1 + N d ⇒ a 1 = 2 5 − 2 N d
Inserting the second in the first equation and using ∣ x ∣ = N ∣ d ∣ , we get
1 0 N = ( 2 5 − 2 N d ) ( 2 5 + 2 N d ) 3. Binomi = 6 2 5 − 4 x 2 ⇒ ∣ x ∣ = 2 5 0 0 − 5 2 N N = 4 0 0 0 = 3 0
Problem Loading...
Note Loading...
Set Loading...
d 1 ( a 2 a 1 a 2 − a 1 + a 3 a 2 a 3 − a 2 + ⋯ + a 4 0 0 1 a 4 0 0 0 a 4 0 0 1 − a 4 0 0 0 ) = 1 0
= d 1 ( a 1 1 − a 2 1 + a 2 1 − a 3 1 + ⋯ + a 4 0 0 0 1 − a 4 0 0 1 1 ) = 1 0
= d 1 ( a 1 1 − a 4 0 0 1 1 ) = 1 0
= d 1 ( a 1 a 4 0 0 1 a 4 0 0 1 − a 1 ) = 1 0
= a 1 a 4 0 0 1 4 0 0 0 = 1 0 ( a s a 4 0 0 1 = a 1 + 4 0 0 0 d )
a 1 a 4 0 0 1 = 4 0 0
a 2 + a 4 0 0 0 = 5 0
⟹ ( a 1 + d ) + ( a 1 + 3 9 9 9 d ) = 5 0
⟹ a 1 + a 4 0 0 1 = 5 0
( a 1 − a 4 0 0 1 ) 2 = ( a 1 + a 4 0 0 1 ) 2 − 4 a 1 a 4 0 0 1
∣ a 1 − a 4 0 0 1 ∣ = 3 0